Meat quality of non-castrated males (Holstein x Zebu), fattened in a silvopastoral system - Iraola, J.; García Orta, Yenny; Fraga, L. M.; Hernández-Báez, J. L. (Cuban Journal of Agricultural Science, 2021)
Meat quality of non-castrated males in finishing stage was evaluated in a silvopastoral system with Leucaena leucocephala, supplemented with corn meal. Thirty-nine animals of the same genetic group (5/8 Holstein x 3/8 Zebu) were used, sacrificed in three groups, of 13 animals each, at different ages (25, 29 and 33 months, respectively), according to the technical standards of the Meat Center of the Institute of Animal Science of the Republic of Cuba. Analysis of variance was performed to evaluate instrumental (color, temperature, pH, texture) and sensory indicators in meat samples taken from the Longissimus dorsi muscle between the tenth and thirteenth rib. The criterion of 60 randomly selected consumers was analyzed for the evaluation. The pH was also determined in two carcass muscles (Semimembranosus and Longissimus dorsi). A difference (p <0.01) was observed in the luminosity indicator (L*) between the youngest age group compared to the oldest. Tenderness values differed (p <0.01) among all groups slaughtered at 25, 29 and 33 months (7.47, 8.82 and 9.75 kg, respectively). The youngest animals showed lower values of tenderness and greater luminosity with respect to the older groups. Keywords: cattle, grazing, beef